Records of the South Sea Company - South Sea Company
Correspondence (1738-1739) of company representatives relating to financial negotiations with the Spanish court and photocopies of investors' authorizations to their agents for transactions involving South Sea Company stock. Agents represented include John Conduitt, John Grigsby, Robert Knight, and Charles Lockyer.
In part, negative photocopies produced with the permission of Charles D. Faulkner.
British company founded in 1711 to trade, chiefly in slaves, with Spanish America. The resulting speculation mania that led to ruin for many investors was known as the South Sea Bubble. Company dissolved in 1753.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Conduitt, John, -- 1688-1737.; Grigsby, John; Knight, Robert, -- 1675-1744.; Lockyer, Charles; Slave trade; South Sea Bubble, Great Britain, 1720.; Great Britain -- Economic conditions -- 18th century; Great Britain -- Foreign relations -- Spain; Spain -- Colonies -- America; Spain -- Foreign relations -- Great Britain